Perception of soil quality in agroecological and conventional horticultural systems of Chaco province (Argentina) - Schahovskoy, Nara Cecilia; Giuffré, Lidia; Rojas, Julieta Mariana; Toledo, Diana Marcela (IOSR, 2023)
Environmental and socioeconomic crisis facing industrialized agriculture and food production has led to araise ofagroecology. Horticultural production systems can be grouped into conventional (CO) or agroecological (AE), based on management and technologies used.It is important to mention that in the present work the use of the term agroecological instead of organic pretends to differentiate diversified systems based on local knowledge of small scale, from certified organic systems that mainly perform input substitution and / or aredestined for export. The importance of this characterization lies mainly in the environmental and social consequences of each of these systems that produce food and employ a large amount of labor. Soil management is a key tool to reach sustainability and farmer vision about soil health is a cultural product. The objectives of this study were to describe social profile of AE and CO horticulturists of Chaco (Argentina) and to recognize how such farmers perceive soil quality (SQ) by means of surveys.Family farming was predominant. All farmers responded to a low-income state and study level was diverse. AE farmers were older. CO work for the markets, AE mainly for own consumption. In relation to soil, they did not perceive worms and erosion signs; they recognized the compaction and the presence of crust. Surface coverage was more important for AE farmers. Smell was well- known by all and majority tried to classify texture and detected soil aeration variations. SQ indicators with greater differences perception were surface crust, texture, aeration and soil color.